Assessing Health and Safety Requirements in Construction Contracts in Botswana - Mwanaumo, Erastus; ., Jan-Harm Pretorius (Journal of Economics and Behavioral Studies, 2014)
The purpose of this study was to investigate the effect of contractor selection andrequirements on Health and Safety compliance in Botswana. Literature was reviewed, a questionnairesurvey was conducted and the statistical analysis undertaken. According to Murie (2007), one of the weaknesses of adopting traditional procurement approach is that the successful tender will frequently be the one that, among others, does not provide H&S protective equipment or have insurance coverage for accidents, and has the largest proportion of informal workers, who are not covered in practice by any legal or social protection. The study has provided usefulinformation involving key stakeholders involvement in H&S performance in constructionindustry. The traditional method could thus impede on Health and Safety management from project preplanningthrough to construction on site.